Konsep Pernikahan Dini dalam Hukum Keluarga Islam: Dari Konteks Historis Masa Nabi ke Regulasi Modern Berbasis Maqāṣid al-Syarī'ah - Dian Galuh Ayu Candra (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2026)
This study analyzes the transformation of the concept of early marriage in Islamic family law from the time of Prophet Muhammad to the modern era, focusing on the shift in marriage eligibility indicators from baligh (biological) to numerical age limits (19 years) under Law No. 16 of 2019. Employing a qualitative library research method, this study integrates historical, hermeneutical, comparative, and maqāṣid al-sharī'ah approaches. The findings reveal that the practice of early marriage during the Prophet's time was a contextual sunnah, not a universal normative prescription, thus allowing flexibility to adapt to changing times. Modern regulations restricting the age of marriage do not contradict sharī'ah; rather, they represent a progressive implementation of sharī'ah's objectives, particularly the protection of life, intellect, and lineage. The maqāṣid approach and the legal maxim dar'u al-mafāsid provide theological legitimacy for the state to impose restrictions to prevent greater harm. This study contributes to the development of uṣūl al-fiqh by demonstrating that collective ijtihad through legislative mechanisms can serve as an instrument for adapting Islamic law to contemporary social realities. Practically, it implies strengthening the capacity of religious court officials, public education based on maqāṣid, and regulatory harmonization. Further research is recommended to explore the effectiveness of policy implementation at the grassroots level and comparative studies across Muslim countries.